Merger and innovation: the case of the oil and gas industry - Anindhito, Rezki, author; Kling, Robert W., advisor; Mushinski, David, committee member; Olienyk, John P., committee member; Ryan, Patricia A., committee member; Weiler, Stephan, committee member (Colorado State University. Libraries, 2010)
Many studies in the late 1990’s concerning the internet and information technology industries show that innovation is the main reasons for company mergers. This dissertation attempts to explain whether merger activities in the oil and gas industry were motivated for the same main reasons as merger activities in the internet and information technology industries. The dissertation is divided into two parts. The first part of the study, using the event study and panel data methodology, examines whether positive impact hypotheses dominate the merger activities. The four benchmark models for normal returns. Market Model (MM), Capital Asset Pricing Model (CAPM), Fama-French Three Factors Model and Fama-French Four Factors Model are used to calculate Cumulative Abnormal Return (CAR). The CAR results from Market Model are the same as the other three normal return models. The only difference is the magnitude of CAR on different models which tend to be smaller as more variables were included in the equation. The CAR results are also in accordance with the fourth and fifth wave theory of mergers. In the second part, using the probit and panel data method, the study tries to explain the relationship between innovation and merger activities. The result shows that innovation can have two opposite effect to merger. We believe that our findings can only explain two from several motivations for merger waves and only focus on the positive impact hypothesis of merger. Therefore, further research is still necessary to examine for other motivations and also to test whether our conclusion also applies to other industries. Additional study on the negative impact hypothesis of merger is also desired to increase our knowledge on merger theory.
Covers not scanned.
Keywords: Petroleum industry and trade -- Mergers; Consolidation and merger of corporations; Technological innovations